Copyright Infringements in Turkey: An Evaluation within the Framework of Supreme Court Decisions - Turan, Metin; Yılmaz, Bülent (Information World, 2014)
In this article, issues of copyright applications within the scope of the provisions which are in the Law On Intellectual and Artistic Works (FSEK) and contain criminal articles were examined. In the framework of the study, Supreme Court’s Decisions dating to 2000 and after, which located in databases, particularly FSEK’s 71, 72 and 81th articles including other articles related, were also evaluated and, results such as copyright infringements, persuant to before mentioned law’s articles in the scope of copyright, are in which areas intensified and how often occured, i.e. their frequencies, were given. According to these results obtained, the vast majority of infringements or problems are about banderole (71%).